2018
DOI: 10.7717/peerj.5383
|View full text |Cite
|
Sign up to set email alerts
|

The appropriateness of ceftriaxone and metronidazole as empirical therapy in managing complicated intra-abdominal infection—experience from Western Health, Australia

Abstract: PurposeThis study aims to assess the microbiological profile, antimicrobial susceptibility and adequacy of intravenous ceftriaxone and metronidazole as empirical therapy for surgical patients presenting with complicated intra-abdominal infection.MethodsThis retrospective audit reviews the microbiological profile and sensitivity of intra-abdominal cultures from adult patients with complicated intra-abdominal infection who presented to the emergency department at Western Health (Melbourne, Australia) between Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Current guidelines from SIS-IDSA and WSES recommend a several antibiotics regimen for community-acquired complicated appendicitis [ 3 - 5 ]. Among these regimens, the combination of ceftriaxone and metronidazole has been reported as appropriate in comparison with the past regimen, with a rate of IEAT reported at 4.1% (2 of 49) [ 14 , 15 ]. In this study, the rate of IEAT was 31.2% (54 of 173) using the same antibiotic regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines from SIS-IDSA and WSES recommend a several antibiotics regimen for community-acquired complicated appendicitis [ 3 - 5 ]. Among these regimens, the combination of ceftriaxone and metronidazole has been reported as appropriate in comparison with the past regimen, with a rate of IEAT reported at 4.1% (2 of 49) [ 14 , 15 ]. In this study, the rate of IEAT was 31.2% (54 of 173) using the same antibiotic regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the isolation of Enterococcus in patients with IAIs results in treatment failure or increased mortality,293031 while others demonstrated no association with mortality 3233. Furthermore, some studies have shown equivalent therapeutic effects among empiric antibiotic regimens, regardless of the antimicrobial activity against enterococci 34353637. At present, prominent guidelines recommend empirical anti-enterococcal therapy for patients with nosocomial IAIs and severe community-acquired IAIs 1028…”
Section: Discussionmentioning
confidence: 99%
“…However, AP must be stopped within 24 hours of the procedure to prevent the emergence of resistant bacteria (15). Ceftriaxone and metronidazole were commonly used antibiotics, likely due to their indications extending to intra-abdominal infections (16).…”
Section: Discussionmentioning
confidence: 99%